Genome‐Wide Association Study in an Amerindian Ancestry Population Reveals Novel Systemic Lupus Erythematosus Risk Loci and the Role of European Admixture. Issue 4 (April 2016) - Alarcón‐Riquelme, Marta E.; Ziegler, Julie T.; Molineros, Julio; Howard, Timothy D.; Moreno‐Estrada, Andrés; Sánchez‐Rodríguez, Elena; Ainsworth, Hannah C.; Ortiz‐Tello, Patricia; Comeau, Mary E.; Rasmussen, Astrid; Kelly, Jennifer A.; Adler, Adam; et al.
Abstract : Objective: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with a strong genetic component. We undertook the present work to perform the first genome‐wide association study on individuals from the Americas who are enriched for Native American heritage. Methods: We analyzed 3, 710 individuals from the US and 4 countries of Latin America who were diagnosed as having SLE, and healthy controls. Samples were genotyped with HumanOmni1 BeadChip. Data on out‐of‐study controls genotyped with HumanOmni2.5 were also included. Statistical analyses were performed using SNPtest and SNPGWA. Data were adjusted for genomic control and false discovery rate. Imputation was performed using Impute2 and, for classic HLA alleles, HiBag. Odds ratios (ORs) and 95% confidence intervals (95% CIs) were calculated. Results: The IRF5–TNPO3 region showed the strongest association and largest OR for SLE (rs10488631: genomic control–adjusted P [ P gcadj ] = 2.61 × 10 −29, OR 2.12 [95% CI 1.88–2.39]), followed by HLA class II on the DQA2–DQB1 loci (rs9275572: P gcadj = 1.11 × 10 −16, OR 1.62 [95% CI 1.46–1.80] and rs9271366: P gcadj = 6.46 × 10 −12, OR 2.06 [95% CI 1.71–2.50]). Other known SLE loci found to be associated in this population were ITGAM, STAT4, TNIP1, NCF2, and IRAK1 . We identified a novel locus on 10q24.33 (rs4917385: P gcadj = 1.39 × 10 −8 ) with an expression quantitative trait locus (eQTL) effect ( P eqtl = 8.0 × 10 −37 at USMG5/miR1307 ), and several new suggestive loci. SLE risk loci previously identified in Europeans and Asians were corroborated. Local ancestry estimation showed that the HLA allele risk contribution is of European ancestral origin. Imputation of HLA alleles suggested that autochthonous Native American haplotypes provide protection against development of SLE. Conclusion: Our results demonstrate that studying admixed populations provides new insights in the delineation of the genetic architecture that underlies autoimmune and complex diseases.